Transcending gender ideology : a philosophy of sexual difference - Malo, Antonio (The Catholic University of America Press, 2020)
"Rejecting both naturalistic and gendered approaches to sexuality, Malo posits a holistic vision of sexuality as a "sexed condition," received at birth and developed and matured through family models, personal experiences, and relationships"--